2016
DOI: 10.14257/ijunesst.2016.9.2.18
|View full text |Cite
|
Sign up to set email alerts
|

The Antecedent and Consequences of Brand Image in a Low-Priced Cosmetic Brand of South Korea: The Moderating Effect of Gender

Abstract: We performed a study to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Likewise, the results of Nasib and Amelia's research (2018) confirm that campus image has a positive and significant influence on student satisfaction. However, contrary to the results of a study conducted by Chung, et al (2016) found that brand image had a positive effect on loyalty but did not affect customer satisfaction.…”
Section: Discussioncontrasting
confidence: 96%
“…Likewise, the results of Nasib and Amelia's research (2018) confirm that campus image has a positive and significant influence on student satisfaction. However, contrary to the results of a study conducted by Chung, et al (2016) found that brand image had a positive effect on loyalty but did not affect customer satisfaction.…”
Section: Discussioncontrasting
confidence: 96%
“…The perception a consumer holds regarding the veracity of online review is considered as the review credibility (Erkan and Evans 2016). Several research studies (Chung , Yu , Kim and Shin (2016) define credible online reviews as a review that the consumers perceive as truthful, logical, and believable. Past research defines credibility to be associated with consumers' perception and evaluation and not as a direct measure of the reality of reviews.…”
Section: Online Reviews and Customer Loyaltymentioning
confidence: 99%
“…In addition, image also has been found to have an impact on perceived quality (Konuk, 2018), satisfaction (Lahap, Ramli, Radzi, Said, & Zain, 2016;Sallam, 2016) and loyalty (Chung, Yu, Kim, & Shin, 2016;Farida & Ardyan, 2018). In general, this is valid especially in the case of Islamic bank in which the services delivered are difficult to be evaluated, and customers are said to be having limited understanding and knowledge on the products offered, which resulted in an image being the most important driver of customer's future behaviour (Prayag, Hosany, Muskat, & Del Chiappa, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%